Two dogs in a trench coat go on a class trip - Falatko, Julie (Falatko, Julie. Two dogs in a trench coat., 2019)
It is field trip day to the city museum, and while Stewart expects a boring day of facts and learning, Waldo and Sassy are looking forward to lunch; then they find that the dinosaur room is full of tempting bones, the astronaut boots are good for chewing, and one of the dioramas features a squirrel on a sidewalk, but the highlight is the delicatessen--if only Waldo and Sassy's disguise can fool the guards who are searching for two dogs.